A lipidated form of the extracellular domain of influenza M2 protein as a self-adjuvanting vaccine candidate. Issue 30 (9th July 2015) - Zeng, Weiguang; Tan, Amabel C.L.; Horrocks, Kylie; Jackson, David C.
Highlights: Lipopeptides based on the extracellular domain of influenza M2 protein constructed. Immunization of the lipopeptides protects mice against lethal viral challenge. Higher IgA and IgG2b antibodies in BAL by the i.n. immunization than the s.c. route. i.n. immunization protects mice better against viral challenge than by s.c. route. Viral challenge boosts anti-M2e antibody specificity introduced by M2e immunization. Abstract: The highly conserved extracellular domain of Matrix protein 2 (M2e) of influenza A virus has been previously investigated as a potential target for an universal influenza vaccine. In this study we prepared four lipopeptide influenza vaccine candidates in which the TLR2 agonist S -[2, 3-bis(palmitoyloxy)propyl] cysteine, (Pam2Cys) was attached to either the N- or C-terminus of the M2e consensus sequence SLLTEVETPIRNEWGCRCNDSSDP and its analogue sequence with the two cysteine residues replaced with serine residues. The results of animal study show that each of these lipopeptides induced strong M2e-specific antibody responses in the absence of extraneous T helper cell epitope(s) which are normally incorporated in the previous studies or addition of extraneous adjuvant and that these antibodies are protective against lethal challenge with influenza virus. Comparison of different routes of inoculation demonstrated that intranasal administration of M2e lipopeptide induced higher titers of IgA and IgG2b antibodies in the bronchoalveolar lavage than did subcutaneous vaccination and was better at mitigating the severity of viral challenge. Finally, we show that anti-M2e antibody specificities absent from the antibody repertoire elicited by a commercially available influenza vaccine and by virus infection can be introduced by immunization with M2e-lipopeptide and boosted by viral challenge. Immunization with this lipidated form of the M2e epitope therefore offers a means of using a widely conserved epitope to generate protective antibodies which are not otherwise induced.